Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1245/s10434-013-3413-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Multidisciplinary Hepatocellular Carcinoma Clinic is Associated with Improved Clinical Outcome

Abstract: Purpose To evaluate differences in overall survival in patients with hepatocellular carcinoma (HCC) after the establishment of a multidisciplinary clinic (MDC) for HCC. Methods Patient demographic and tumor characteristics of 355 patients diagnosed with HCC were collected between October 2006 and September 2011. Patients diagnosed after the initiation of the HCC MDC on October 1, 2010, were compared to patients diagnosed in the 4 years before. Patient demographics, tumor characteristics, treatment regimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(158 citation statements)
references
References 18 publications
5
151
0
2
Order By: Relevance
“…These associations may be driven by several factors such as higher rates of multidisciplinary care or better management of liver complications, which have been shown to improve survival (32) ; alternatively, this association may simply represent a referral or selection bias, with healthier patients who have a better prognosis being more likely to seek care at a tertiary care center. Further studies are needed to explore these associations; if confirmed and related to a difference in care delivery, this may suggest that treatment of advanced HCC patients be focused in expert, high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…These associations may be driven by several factors such as higher rates of multidisciplinary care or better management of liver complications, which have been shown to improve survival (32) ; alternatively, this association may simply represent a referral or selection bias, with healthier patients who have a better prognosis being more likely to seek care at a tertiary care center. Further studies are needed to explore these associations; if confirmed and related to a difference in care delivery, this may suggest that treatment of advanced HCC patients be focused in expert, high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…During the 6-week interval, patients did not undergo any specific treatment. This interval is much shorter than the average time to treatment after HCC diagnosis14 15 and therefore no ethical issues were raised by IRB. After the second CT, patients were treated according to international guidelines1 and were monitored every 3 months unless their clinical condition required more frequent monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…In another research on evaluating differences in overall survival in patients with HCC after the establishment of a MDT for HCC, a total of 105 patients were diagnosed in the time period after HCC MDT initiation compared to 250 patients in the previous 4 years. The result showed that patients diagnosed after HCC MDT initiation had a median survival of 13.2 months compared to the 4.8 months observed in patients diagnosed before MDT formation [14]. These evidences suggested that the MDT model could benefit patients with HCC.…”
Section: Discussionmentioning
confidence: 89%